Ask Dr. K. Fisher about dinosaurs - Llewellyn, Claire; Sheppard, Kate (Boston, Mass. : Kingfisher, 2007)
Uses letters to a fictional bird character named Dr. Fisher to answer questions children often have about dinosaurs.
Includes index.
3.0
K-3
Keywords: Dinosaurs -- Miscellanea -- Juvenile literature; Dinosaurs -- Miscellanea; Dinosaurs -- Miscellanea